The independence of Rhodesia in Salazar's strategy for southern Africa - Barroso, L. (2014)
The prime hypothesis of this text is that portugal's support of southern rhodesia after the unilateral declaration of independence (november 11, 1965) was part of a national strategy that aimed to link angola and mozambique to the future of the 'white man' in southern africa. This strategy was first conceived in early 1962 and was made operational from mid-1964 when ian smith came to power in southern rhodesia with the promise that he would do everything possible to liberate the country from great britain and maintain white supremacy. Our analysis relies mostly on portugal's legationdocumentation in salisbury and reveals three main reasons of salazar's strategy decision. First, salazar was aware that keeping ian smith in power would mean withdrawing the 'one man one vote' option that london intended, strengthening the maintenance of the colonial policy in angola and mozambique backed by legislation and propaganda that proclaimed multi-racialism. Second, salazar considered that although there would be a strong international reaction to smith's decision, led mainly by britain and the united states, it would not last long due to the strategic considerations of the cold war that proved to be more important than the aspirations of black populations. Third, salazar believed that the success of the war effort, initiated in 1961 in angola and extended to guinea and mozambique, relied on south africa's contribution, and that a strong tie with ian smith would mean closer links with south africa.